Scaling of differential equations - Langtangen, Hans Petter; Pedersen, Geir K (Simula SpringerBriefs on Computing, 2016)
This work serves both as a reference for various scaled models with corresponding dimensionless numbers, and as a resource for learning the art of scaling. A special feature of the book is the emphasis on how to create software for scaled models, based on existing software for unscaled models.